2013
DOI: 10.1242/jcs.126086
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of polyglutamine aggregates in neuronal cells occurs in tunneling nanotubes

Abstract: SummaryHuntington's disease (HD) is a dominantly inherited neurodegenerative disease caused by CAG expansion in the huntingtin gene, which adds a homopolymeric tract of polyglutamine (polyQ) to the encoded protein leading to the formation of toxic aggregates. Despite rapidly accumulating evidences supporting a role for intercellular transmission of protein aggregates, little is known about whether and how huntingtin (Htt) misfolding progresses through the brain. It has been recently reported that synthetic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
182
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(191 citation statements)
references
References 42 publications
(70 reference statements)
6
182
0
2
Order By: Relevance
“…Although there is abundant evidence that spreading occurs through synaptic connections, other potential mechanisms include spreading between cells via exosomes (43,44) or tunneling nanotubes (45). In the current study, we find unique patterns of spreading when mutant Htt is expressed in different subsets of neurons in the brain.…”
Section: Discussionmentioning
confidence: 52%
“…Although there is abundant evidence that spreading occurs through synaptic connections, other potential mechanisms include spreading between cells via exosomes (43,44) or tunneling nanotubes (45). In the current study, we find unique patterns of spreading when mutant Htt is expressed in different subsets of neurons in the brain.…”
Section: Discussionmentioning
confidence: 52%
“…However, others 10 also find low proportions of cell-to-cell transfer of TDP-43 aggregates in 2D culture. Moreover, similar experiments with Htt polyQ showed 3.7% of cells had both donor and recipient constructs, 19 indicating that in general these types of experiments have low rates of transfer, likely due to the fact that the culture is 2D and that the cells interface with media and the plastic more than adjacent cells.…”
Section: Discussionmentioning
confidence: 88%
“…Transfer events were quantified as the percentage of transfected cells positive for both tGFP/tdTomato using a similar strategy previously published for Htt. 19 While control cells showed negligible numbers of cells measured as 2 colored (Fig. 2 D), greater than 10% of transfected cells in the co-cultured cell populations contained both fusion proteins at 24 h. The number of cells containing both fusion proteins dropped at 72 h, suggesting that transfer of pathogenic proteins may be particularly toxic.…”
Section: Tdp-43 Can Transfer From Cell-to-cellmentioning
confidence: 91%
“…133 By contrast, expression of polyQ-HTT fragments in CAD neuronal cells and primary cerebellar granule neurons in vitro did result in spontaneous and efficient transfer to neighboring cells that did not require release from dying cells. 134 In this instance, transfer required cell-to-cell contact and aggregates were found in tunneling nanotubes, which were increased by polyQ-HTT expression. 134 Perhaps providing the most compelling evidence to date of propagation of polyQ-HTT in vitro, a new study has reported that when hESC-derived neurons were introduced into brain slices from HD disease model R6/2 mice, the hESC-derived neurons developed HTT aggregates and exhibited signs of toxicity.…”
Section: Primary Cilia: Secretory Organelles?mentioning
confidence: 91%
“…134 In this instance, transfer required cell-to-cell contact and aggregates were found in tunneling nanotubes, which were increased by polyQ-HTT expression. 134 Perhaps providing the most compelling evidence to date of propagation of polyQ-HTT in vitro, a new study has reported that when hESC-derived neurons were introduced into brain slices from HD disease model R6/2 mice, the hESC-derived neurons developed HTT aggregates and exhibited signs of toxicity. 135 Similarly, when R6/2 cortical brain slices were co-cultured with striatal brain slices from WT mice, polyQ-HTT aggregates developed in the WT striatal neurons.…”
Section: Primary Cilia: Secretory Organelles?mentioning
confidence: 91%